Chemical composition and antibacterial activities of essential oils from fruits of Melicope pteleifolia (Champ. Ex Benth.) T.G. Hartley grown in Lam Dong Province, Vietnam - Binh, Hoang Thi; Tram, Tran Thi Bao; Dai, Do Ngoc; Tien, Vuong Thuy; Tam, Le Minh; Ngoc, Nguyen Van (Academia Journal of Biology, 2020)
In the present study, chemical composition and antibacterial properties of essential oil obtained from the aerial parts of the Melicope pteleifolia (Champ. ex Benth.) T.G Hartley in Dalat were evaluated. Essential oil was isolated through hydro-distillation. Twenty-nine constituents comprising 100% of the essential oil were characterized by gas chromatography/mass spectrometry (GC-MS) techniques. The major compounds in the essential oil were (+)-Sabinene (34.73%), Cis-α-bergamotene (13.15%), Z-α-trans-bergamotol (5.28%), β-mycrene (4.98%), and 1,3,6-octatriene, 3,7-dimethyl-(4.71%). Antibacterial activities of Melicope pteleifolia essential oil were investigated against Gram-positive and-negative bacteria. Results showed significant activities against Streptococcus pyogenes and Escherichia coli using an agar well diffusion method. The application of this essential oil in preventing and eliminating bacteria could be useful in fields as medicine and cosmetics.